Childhood Traumatic Experiences, Dissociative Symptoms, and Dissociative Disorder Comorbidity Among Patients With Panic Disorder: A Preliminary Study. Issue 4 (8th August 2015) - Ural, Cenk; Belli, Hasan; Akbudak, Mahir; Tabo, Abdulkadir
Abstract : This study assessed childhood trauma history, dissociative symptoms, and dissociative disorder comorbidity in patients with panic disorder (PD). A total of 92 psychotropic drug–naive patients with PD, recruited from outpatient clinics in the psychiatry department of a Turkish hospital, were involved in the study. Participants were assessed using the Structured Clinical Interview for DSM–IV Dissociative Disorders (SCID-D), Dissociation Questionnaire, Panic and Agoraphobia Scale, Panic Disorder Severity Scale, and Childhood Trauma Questionnaire. Of the patients with PD, 18 (19%) had a comorbid dissociative disorder diagnosis on screening with the SCID-D. The most prevalent disorders were dissociative disorder not otherwise specified, dissociative amnesia, and depersonalization disorders. Patients with a high degree of dissociation symptoms and dissociative disorder comorbidity had more severe PD than those without ( p < .05). All of the childhood trauma subscales used were correlated with the severity of symptoms of dissociation and PD. Among all of the subscales, the strongest relationship was with childhood emotional abuse. Logistic regression analysis showed that emotional abuse and severity of PD were independently associated with dissociative disorder. In our study, a significant proportion of the patients with PD had concurrent diagnoses of dissociative disorder. We conclude that the predominance of PD symptoms at admission should not lead the clinician to overlook the underlying dissociative process and associated traumatic experiences among these patients.